ASEAN's "actorness" and "effectiveness" regarding the COVID-19 pandemic. Issue 1 (1st March 2022) - Rollet, Vincent
Abstract: The COVID-19 pandemic represents a new significant test for the role of Association of Southeast Asian Nations (ASEAN) in regional health governance in Southeast Asia. Assessing ASEAN's role during the pandemic through the concepts of "actorness" and "effectiveness, " the article argues that while ASEAN displayed all the attributes of actorness during the COVID-19 pandemic when it comes to its effectiveness, the capacity of the regional institution to reach the objectives it committed to has been rather limited. Explaining the reasons for such "effectiveness–expectation gap" and, considering the last policy development in the region related to regional health coordination, the article identifies several conditions for ASEAN to strengthen its capacity to act effectively on regional health cooperation, and to contribute to the strengthening of a regional health response to a possible future epidemic threat. Resumen: El COVID-19 representa una nueva e importante prueba para el papel de la ASEAN en la gobernanza sanitaria regional. Al evaluar su papel durante la pandemia a través de los conceptos de "actuación" y "eficacia", el artículo sostiene que, si bien la ASEAN mostró todos los atributos de actoría durante la pandemia, en lo que respecta a su eficacia, su capacidad para alcanzar los objetivos a los que se comprometió ha sido limitada. Explicando las razones de esa "brecha entre eficacia y expectativas" y considerando el último desarrollo de políticas de coordinación sanitaria regional, el artículo identificó varios prerrequisitos como ineludibles en su búsqueda por reforzar la eficacia para garantizar la cooperación sanitaria regional en el Sudeste Asiático y mejorar la respuesta regional ante una próxima amenaza sanitaria. Résumé: La pandémie de COVID-19 représente un test significatif pour apprécier le rôle de l'Association des nations de l'Asie du Sud-Est (ASEAN) au sein de la gouvernance sanitaire régionale en Asie du Sud-Est. En évaluant le rôle de l'ASEAN pendant cette pandémie à travers les concepts d'actorness (capacité à agir) et d'effectiveness (efficacité), cet article montre que si l'ASEAN a exprimé sa capacité à agir pendant cette crise sanitaire, son efficacité, i.e son aptitude à atteindre les objectifs qu'elle s'est fixés, a été plutôt limitée. Les raisons d'un tel écart entre efficacité et attentes (effectiveness-expectations gap) sont expliquées dans l'article qui identifie plusieurs conditions pour que l'ASEAN contribue efficacement au renforcement d'une réponse sanitaire régionale indispensable face à une éventuelle prochaine menace épidémique.